Implementation of Sanctions for Health Facilities that Have Not Implemented Electronic Medical Records (EMR) - Hari santoso (Borong Newinera Publisher, 2024)
Hospitals are health care institutions that provide inpatient, outpatient, and emergency services. One of the services in the hospital is medical record services. This medical record stores various records regarding the identity, examination, treatment, actions, and other services performed on the patient. Along with the development of technology, medical records are present in digital form or called Electronic Medical Records (RME). The purpose of this study is to analyze sanctions for health facilities that have not implemented Electronic Medical Records (RME). The research method used is a literature review with a qualitative approach. The results show that with the regulatory provisions and sanctions, the implementation of RME is expected to improve the overall standard of health services. In accordance with circular number HK.02.01/MENKES/1030/2023, health facilities that do not comply with the RME implementation deadline may face administrative sanctions, including recommendations for revocation of accreditation status. These sanctions also apply to health facilities that have not integrated with the SATUSEHAT Platform by March 2024 or have not submitted patient visit data as required. This regulation is not only a guide, but also an encouragement for health service delivery to become more sophisticated, efficient, and safe through the implementation of RME.